BTS Fanboy's Self-Disclosure on Instagram - Aryani, Choyriyah Dwi; Aisyah, Vinisa Nurul (Universitas Muhammadiyah Surakarta, 2023)
Fanboy refers to a man who likes an artist or idol group. However, BTS fanboys are still getting stereotyped about their masculinity by society especially on social media, like an Instagram. The purpose of this study is to find out how BTS fanboy's self-disclosure on Instagram. This study uses Johari Window's self-disclosure theory. This theory explains about 4 areas, namely open area, blind area, hidden area, and unknown area. This research is one of qualitative research. The sampling technique was implemented by using snowball sampling method with four informants who are BTS fanboys and they have been active as fanboys of BTS on Instagram. The informants of this study also around 17-25 years old. Data collection techniques was using interview methods. The results of this study show that in the open area, BTS fanboys try to fight stereotypes about the masculinity of BTS fanboys on Instagram. In the blind area, fanboys get stereotypes from society about their questioned masculinity when they become fanboys. Then in the hidden area, fanboys used to hide themselves as fanboys because they were afraid of getting stereotypes from society. And in the unknown area of this study was found that fanboys didn't know how long they would stop being fanboys and would continue to fight the stereotypes that they received.